28 USC § 1782—looking for consensus. (22nd October 2019) - Stute, David J
Abstract: Since the 1948 enactment of 28 USC § 1782 in the United States, no consensus has emerged as to the availability of federal court discovery to parties in private foreign or international arbitral proceedings. This year, within months of one another, six federal courts have issued rulings that are widely inconsistent on the availability of section 1782 discovery. The courts have ruled that a proceeding before a private international arbitral tribunal is eligible for section 1782 discovery; that, categorically, no such discovery is available; that the definition of private arbitral tribunal applies to CIETAC; and that discovery is available by virtue of a party's parallel pursuit of discovery through foreign civil proceedings. As these cases demonstrate, recent US court decisions have brought no predictability, let alone certainty, to the subject. Congress, on the other hand, could and should amend the statute so as to include private tribunals in the scope of section 1782. This article discusses the case law's state of disarray; proposes a legislative solution; considers the proposed amendment's merits; and advocates for Congress to act.